GENERIC INTEGRITY AND FIDELITY IN THE ADAPTATION OF UNBROKEN: A BIOPIC OF AN UNYIELDING SURVIVOR - Dr. Umara Shaheen; Dr. Nadia Anwar (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study aims to analyze the film adaptation of Hillenbrand’s bestselling book "Unbroken: A WWII Story of Survival, Resilience, and Redemption" (2010) as portrayed in the biopic "Unbroken: The Unbelievable True Story" (2014). The selected movie depicts the remarkable life of Louis Zamperini, an Olympic runner and Army Air Forces bombardier, who endured extensive abuse and dehumanization as a Prisoner of War (POW) at a Japanese war camp during WWII. While staying faithful to the book, the movie also adheres to the conventions of two modes of adaptation: transposition and commentary, aligning with the medium specificity approach. The researchers discuss the biopic’s narrative time frame, narrative structure, and historical accuracy, upholding its generic integrity and independence.